Pengaruh E-Learning, Pembelajaran Langsung, dan Faktor Gaya Kognitif Terhadap Hasil Belajar Prakarya Kewirausahaan - Fadlul Amin Nudin; Rufi'i Rufi'i; Djoko Adi Walujo (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2021)
This study aims to see differences in learning outcomes of E-Learning-based and direct learning group entrepreneurship learning outcomes, to see differences in learning outcomes between Field Dependent and Field Independent cognitive styles, and to see E-Learning-based learning interactions, direct, and cognitive styles on learning outcomes. This study used a two-time two factorial quasi-experimental method. The control group uses direct learning, while the experimental group uses E-Learning. Analysis using two-way ANOVA will compare the effect of direct and E-Learning-based learning and cognitive styles on learning outcomes. Results: Ha.1 probability value (p) 0.013 < 0.05 means that there are differences in learning outcomes based on E-Learning and direct learning, Ha.2 probability value (p) 0.004 < 0.05 means that there are differences in learning outcomes between Field Dependent and Field Independent cognitive style, Ha.3 probability value (p) 0.07 > 0.05 means that there is no influence between E-Learning-based, direct and cognitive style learning on learning outcomes.